2019
DOI: 10.1186/s12913-019-3953-0
|View full text |Cite
|
Sign up to set email alerts
|

Can the primary health care model affect the determinants of neonatal, post-neonatal and maternal mortality? A study from Brazil

Abstract: Background The state of São Paulo recorded a significant reduction in infant mortality from 1990 to 2013, but the desired reduction in maternal mortality was not achieved. Knowledge of the factors with impact on these indicators would be of help in formulating public policies. The aims of this study were to evaluate the relations between socioeconomic and demographic factors, health care model and both infant mortality (considering the neonatal and post-neonatal dimensions) and maternal mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
0
14
0
9
Order By: Relevance
“…The BPHS project was designed to achieve the full cycle of health monitoring and healthcare for newborns from pregnancy to neonatal, which could be key to its effectiveness. The evidences in India, 28 Brazil 30 and many LMICs showed that they had achieved significant decrease in NMR through maternal and neonatal health services, at least three times of antenatal care and postpartum care 31 were provided during the whole pregnancy, which confirmed the potential effect of maternal and neonatal health services in reducing NMR.…”
Section: Discussionmentioning
confidence: 75%
“…The BPHS project was designed to achieve the full cycle of health monitoring and healthcare for newborns from pregnancy to neonatal, which could be key to its effectiveness. The evidences in India, 28 Brazil 30 and many LMICs showed that they had achieved significant decrease in NMR through maternal and neonatal health services, at least three times of antenatal care and postpartum care 31 were provided during the whole pregnancy, which confirmed the potential effect of maternal and neonatal health services in reducing NMR.…”
Section: Discussionmentioning
confidence: 75%
“…The intervening factors in the current situation of gestational and congenital syphilis probably derive from the access to and capacity of prenatal care 7 , as well as the coverage of primary health care in the Brazilian state capitals. Maternal and infant mortalities are associated with the inadequacy of prenatal care 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Although São Paulo has the best quality and best levels of neonatal rate when compared to the rest of Brazil, as depicted in Fig. 3 , these events occurred in heterogeneous ways with smaller or even lower reductions in the most vulnerable populations, as the reflection of unfavorable life conditions of the population, health care and socioeconomic inequalities [ 9 ].
Fig.
…”
Section: Dataset Construction and Explorationmentioning
confidence: 99%